Genetic and biological characterisation of a novel South African Plutella xylostella granulovirus (PlxyGV) isolate - Abdulkadir, Fatima (Rhodes University, Faculty of Science, Department of Biochemistry, Microbiology and Biotechnology, 2014)
The diamondback moth, Plutella xylostella (L.) (Lepidoptera: Plutellidae), is an important pest of cruciferous crops worldwide. The prolonged use of synthetic chemical insecticides as a primary means of control has resulted in the development of resistance in pest populations. In addition, the pest has also evolved resistance to the bacterial insecticidal protein of Bacillus thuringiensis which is also widely used as a method of control. Baculoviruses are considered as effective alternatives to conventional methods of control when incorporated into integrated pest management (IPM) programmes. These viruses target the larval stages of insects, are generally host-specific and are safe for use in the environment. This study aimed to isolate a baculovirus from a laboratory-reared P. xylostella colony, characterise it genetically and then evaluate its virulence against neonate and fourth instar larvae. A laboratory colony of P. xylostella was established using pupae and asymptomatic larvae collected from a cabbage plantation outside Grahamstown in the Eastern Cape province of South Africa. The colony flourished in the laboratory due to prime conditions and availability of food. The duration of development from egg to adult was determined by observation and imaging of the various life stages. The mean developmental time from egg to adult was observed to be 14.59 Â± 0.21 days. The population of the insects increased rapidly in number leading to overcrowding of the insect colony, and hence appearance of larvae with viral symptoms. Occlusion bodies (OBs) were extracted from symptomatic larval cadavers and purified by glycerol gradient centrifugation. Analysis of the purified OBs by transmission electron microscopy revealed the presence of a granulovirus which was named PlxyGV-SA. The virus isolate was genetically characterised by restriction endonuclease analysis of the genomic DNA, and PCR amplification and sequencing of selected viral genes. The complete genome sequence of a Japanese P. xylostella granulovirus isolate, PlxyGV-Japan, has been deposited on the GenBank database providing a reference strain for comparison with DNA profiles and selected gene sequences of PlxyGV-SA. BLAST analysis of the granulin gene confirmed the isolation of a novel South African PlxyGV isolate. Comparison of the restriction profiles of PlxyGV-SA with profiles of PlxyGV-Japan and other documented PlxyGV profiles obtained by agarose gel electrophoresis revealed that PlxyGV-SA is a genetically distinct isolate. The data obtained from the sequencing and alignment of ecdysteroid UDP-glucosyltransferase (egt), late expression factor 8 (lef-8) and late expression factor 9 (lef-9) genes with those of PlxyGV-Japan also showed that PlxyGV-SA is a genetically different isolate. In order to determine the biological activity of PlxyGV-SA against neonate and fourth instar P. xylostella larvae, surface dose bioassays were conducted. The median lethal concentration of the virus required to kill 50% (LCâ‚…â‚€) and 90% (LCâ‚‰â‚€) of the larvae was estimated by feeding insects with a range of doses. In addition, the time to kill 50% of the larvae (LTâ‚…â‚€) was determined by feeding insects with the LCâ‚‰â‚€ concentration. Larval mortality was monitored daily until pupation. The data obtained from the dose response assays were subjected to probit analysis using Proban statistical software. The time response was determined using GraphPad Prism software (version 6.0). The LCâ‚…â‚€ and LCâ‚‰â‚€ values for the neonate larvae were 3.56 Ã— 10â µ and 1.14 Ã— 10â · OBs/ml respectively. The LTâ‚…â‚€ was determined to be 104 hours. The neonate larvae were found to be more susceptible to infection than the fourth instar larvae with the same virus concentration. The concentrations used for the neonate larvae assay did not have a significant effect on the fourth instar as no mortality was recorded. This is the first study to describe a novel South African PlxyGV isolate and the results suggest that PlxyGV-SA has significant potential for development as an effective biopesticide for the control of P. xylostella in the field.
Keywords: Diamondback moth; Diamondback moth -- Control -- South Africa; Plutellidae -- Control -- South Africa; Baculoviruses; Cruciferae -- Diseases and pests -- South Africa